INDDEX24 Dietary Assessment Platform - Bell, Winnie (2022)
Winnie Bell POLICY SEMINAR Nudging for Good: AI driven diagnostics and behavior change to improve diets and nutrition JUL 28, 2022 - 12:00 TO 2:00PM EDT